Hemingway and Ho Chi Minh in Paris : The Art of Resistance - Crowe, David (Book collections on Project MUSE., 2020)
Two of the twentieth century's most fascinating figures, grappling with a world in which Western culture adn their respective governments werre failing them, came to Paris at the same time in the 1920s. Hemingway and Ho Chi Minh in Paris tells the untold, engrossing story of these two young men and their journey into the heart of resistance in 1920s Paris.